Effect Of Date Seed Powder On The Time Taken To Tenderize Meat and The Sensory Characteristics - Alsalhi, Ahmed; Sabah M. Al-Shatty; Eman A. Al-Imara; Afrah H. Awadh; Israa A. Salih (Indonesian Journal Publisher, 2025)
This study was conducted to investigate the effect of adding date seed powder to red meat on the time taken to tenderize meat and the sensory qualities. The powder was added at four different levels (0, 10, 20,and 30) %, so that each level represents a separate treatment (T0, T10, T20, T30) % respectively, and with three replicates for each treatment, distributed randomly during cooking, which was done by preparing 300 g of meat for each treatment, at a rate of 100 g / 500 ml of water for each replication, and by the wet cooking method, and using a digital laser cooker; to measure cooking time and evaluate sensory qualities. The results indicated a significant improvement (P≤0.05) in favor of the treatment that included adding 30% of date seed powder in reducing the time taken to tenderize the meat. The powder treatments also contributed to improving the sensory qualities such as color, odor, taste, texture, juiciness, and overall acceptability, specifically when adding the powder at a rate of T20% to the meat sample.